Interleukin-13 and transforming growth factor β synergise in the pathogenesis of human intestinal fistulae. Issue 1 (27th January 2012) - Scharl, Michael; Frei, Sandra; Pesch, Theresa; Kellermeier, Silvia; Arikkat, Joba; Frei, Pascal; Fried, Michael; Weber, Achim; Jehle, Ekkehard; Rühl, Anne; Rogler, Gerhard
Abstract : Objective: Epithelial to mesenchymal transition (EMT) seems to play an important role in the pathogenesis of fistulae, a common clinical complication of Crohn's disease (CD). TGFβ and interleukin-13 (IL-13) have been correlated with the onset of EMT-associated organ fibrosis and high levels of TGFβ have been shown in transitional cells (TCs) lining CD fistula tracts. This study investigated whether IL-13 could be involved in the pathogenesis of CD-associated fistulae. Design: Protein or mRNA levels in HT29 intestinal epithelial cells (IECs) or colonic lamina propria fibroblasts (CLPFs) were studied by western blotting or real-time PCR. CLPFs were isolated from non-inflammatory disease controls or patients with CD with or without fistulae and IL-13 levels were analysed in surgically removed fistula specimens by immunohistochemistry. Results: TGFβ induced IL-13 secretion in CLPFs from patients with fistulising CD. In fistula specimens high levels of IL-13 were detected in TCs covering fistula tracts. In HT29 IEC monolayers, IL-13 induced SLUG and β6-integrin mRNA, which are associated with cell invasion. HT29 spheroids completely disintegrated when treated with TGFβ for 7 days, whereas IL-13-treated spheroids did not show morphological changes. Here, TGFβ induced mRNA expression of SNAIL1 and IL-13, whereas IL-13 elevated SLUG and β6-integrin mRNA. An anti-IL-13 antibody was able to prevent IL-13-induced SLUG expression in HT29 IECs. Conclusions: TGFβ induces IL-13 expression and an EMT-like phenotype of IECs, while IL-13 promotes the expression of genes associated with cell invasion. These findings suggest that TGFβ and IL-13 play a synergistic role in the pathogenesis of fistulae and inhibition of IL-13 might represent a novel therapeutic approach for fistula treatment.